2014
DOI: 10.1111/hdi.12247
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations of depressive symptoms and pain with quality of life in patients receiving chronic hemodialysis

Abstract: Background Depressive symptoms and pain are common in patients on chronic hemodialysis (HD), yet their associations with quality of life (QOL) are not fully understood. We sought to characterize the longitudinal associations of these symptoms with QOL. Methods As part of a trial comparing two symptom management strategies in patients receiving chronic HD, we assessed depressive symptoms using the Patient Health Questionnaire-9 (PHQ-9), and pain using the Short-Form McGill Pain Questionnaire (SF-MPQ) monthly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 56 publications
3
39
1
2
Order By: Relevance
“…As doenças associadas à DRC, como Hipertensão Arterial, dé-ficit visual, diabetes Mellitus, catarata, infarto do miocárdio e insuficiência cardíaca também confirmam como esses pacientes, maioria adultos, homens e hipertensos são mais propensos a essas comorbidades, podendo ou não estarem relacionadas à sua afecção de base renal (18) . As complicações mais comuns da hemodiálise encontradas na literatura foram em ordem decrescente de frequência: hipotensão, cãibras, náuseas e vômitos, cefaleia, dor torácica, dor lombar, prurido, febre e calafrios (19)(20) . (21) .…”
Section: Methodsunclassified
“…As doenças associadas à DRC, como Hipertensão Arterial, dé-ficit visual, diabetes Mellitus, catarata, infarto do miocárdio e insuficiência cardíaca também confirmam como esses pacientes, maioria adultos, homens e hipertensos são mais propensos a essas comorbidades, podendo ou não estarem relacionadas à sua afecção de base renal (18) . As complicações mais comuns da hemodiálise encontradas na literatura foram em ordem decrescente de frequência: hipotensão, cãibras, náuseas e vômitos, cefaleia, dor torácica, dor lombar, prurido, febre e calafrios (19)(20) . (21) .…”
Section: Methodsunclassified
“…The international, prospective, observational study with more than 10,000 patients demonstrated that nearly 20% of the cohort had depression [20] while in study by Weisbord et al [21] , pain is present in about 50% of the dialysis patients. Belayev et al [19] also showed that pain and depressive symptoms are independently associated with HRQOL after assessing the pain and depressive symptoms monthly and HRQOL quarterly for 24 months. Both DOPPS [20] and the study by Weisbord et al [21] demonstrated that depression is associated with increased hospitalization and mortality.…”
Section: Symptoms Associated With Poor Hrqolmentioning
confidence: 97%
“…Depressive symptoms and pain are commonly reported by patients undergoing dialysis [19][20][21] . The international, prospective, observational study with more than 10,000 patients demonstrated that nearly 20% of the cohort had depression [20] while in study by Weisbord et al [21] , pain is present in about 50% of the dialysis patients.…”
Section: Symptoms Associated With Poor Hrqolmentioning
confidence: 99%
“…Depressive symptoms in people with CKD are associated with decreased quality of life [36] and decreased wellbeing [17]. Dialysis nurses should therefore be encouraged to increase people with CKD's happiness through the integration of laughter yoga [37], the Fordyce's happiness program [38], and the visualization of humor ilms [39], during dialysis sessions.…”
Section: Implications For Practicementioning
confidence: 99%